Directorial Vision And Inner Meaning: An Analysis Of Andrew Sarris's Auteur Theory In The Film Sore - Nur Zilla Ramadhani; Maulida Farah Aqilah (International Journal of Technology and Education Research, 2026)
This study aims to uncover the directorial vision and inner meaning in the film Sore: Istri dari Masa Depan by Yandy Laurens, an aspect often overlooked in previous studies that tend to emphasize narrative and commercial dimensions. This research employs a qualitative approach through close reading of the film text as the primary object, combined with Roland Barthes’ semiotic analysis to unpack denotative, connotative, and mythical meanings in several key shots representing the characters’ emotions and conflicts. In addition, Andrew Sarris’s auteur theory is used to trace the consistency of directorial style and to identify interior meaning as a representation of the director’s personal presence within the work. Data were obtained through repeated viewings of the film, comparative analysis with Yandy Laurens’s other works, and interview tracing as supporting data to strengthen the interpretation. The results show that Yandy Laurens holds a directorial vision that places emotional honesty, humanity, and depth of interpersonal relationships above mere visual aesthetics. The use of still shots and silence becomes a distinctive signature functioning as a marker to convey the characters’ inner processes in a deep and reflective manner. Semiotically, each scene presents not only literal meaning but also constructs myths about love, loss, regret, and self-reflection within the context of modern urban human life. This study affirms that the film is a strong manifestation of Yandy Laurens’s auteur signature, positioning film as both a medium of inner reflection and a critique of the existential condition of contemporary humans.